Stealth Surgery in Pediatric Age Group-an Aesthetic Alternative - Saurabh Garge; Geetika Paliwal (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: We used a subcutaneoscopic technique that places incisions at unnoticeable sites to avoid unsightly scars. Materials and Methods: This is a review of five consecutive cases operated by stealth approach between January 2015 and December 2016. Three cases underwent subcutaneoscopic excision of dermoid cyst and two underwent stealth tenotomy for torticollis. All patients underwent stealth surgery as previously described with few technical modifications. Results: All five cases underwent successful subcutaneoscopic surgery without the need for conversion. The mean operative duration of the procedure was 45 min.(Range,40-50min) for the external angular dermoid excision and 67.5 min(Range,60-75 min.) for the sternomastoid tenotomy. There were no complications, and all patients had excellent cosmesis. Conclusion:Subcutaneoscopic excision of dermoid cyst is a technically feasible procedure in pediatric patients and provides excellent cosmesis.